2009
DOI: 10.1080/01635580902850082
|View full text |Cite
|
Sign up to set email alerts
|

The Cancer Preventive Seed Peptide Lunasin From Rye Is Bioavailable and Bioactive

Abstract: Lunasin is a unique 43-amino acid peptide that has been shown to be chemopreventive in mammalian cells and in a skin cancer mouse model against oncogenes and chemical carcinogens. In search for new sources of lunasin and to better understand the role of cereals in cancer prevention, we report here the properties of lunasin from rye. The stability and bioavailability were measured by in vitro digestibility assay using pepsin and pancreatin and feeding rats with lunasin-enriched rye (LER). Inhibition of histone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 18 publications
2
57
0
1
Order By: Relevance
“…Lunasin has been identified in soybean, barley, wheat and rye, and has been subjected to corresponding comparative analysis (24,25). However, due to the genotypic impact of different species, the lunasin content varies between species (26).…”
Section: Characterization Of Lunasinmentioning
confidence: 99%
See 1 more Smart Citation
“…Lunasin has been identified in soybean, barley, wheat and rye, and has been subjected to corresponding comparative analysis (24,25). However, due to the genotypic impact of different species, the lunasin content varies between species (26).…”
Section: Characterization Of Lunasinmentioning
confidence: 99%
“…However, due to the genotypic impact of different species, the lunasin content varies between species (26). The lunasin content in soybean, barley, wheat and rye was determined to be between 0.5 and 8.1, between 0.013 and 0.099, between 0.2 and 0.3, and between 0.045 and 0.150 mg/g seed, respectively (14,25,26). Therefore, soybean and wheat are recognized as the principal sources of lunasin (14).…”
Section: Characterization Of Lunasinmentioning
confidence: 99%
“…In search of natural sources of lunasin besides soybean, a first screening has been carried out using different beans, grains and herbal plants. Lunasin has been found in cereal grains known for its health effects, such as barley, wheat, and rye [24][25][26][27]. Several seeds of oriental herbal and medicinal plants have been analyzed, finding that lunasin is present in all of the Solanaceae family, except L. Chinensis, but not in any of the Phaseolus beans [28].…”
Section: Lunasin: Discovery and Beyondmentioning
confidence: 99%
“…First studies carried out in mice and rats fed lunasin-enriched soy protein found that 35% of ingested lunasin reaches the target tissues and organs in an intact and active form [17,28]. Lunasin from rye and barley have also shown stability towards pepsin and pancreatin in vitro digestion and the liver, kidney, and blood of rats fed with lunasin-enriched rye or barley, respectively, contained this peptide as detected by Western blot [26,27]. Naturally protease inhibitors, such as BowmanBirk protease inhibitor and Kunitz trypsin inhibitor have been demonstrated to exert a protective effect on lunasin against digestion by gastrointestinal enzymes, playing this protection a key role in making lunasin bioavailable [31].…”
Section: Bioavailability Of Lunasinmentioning
confidence: 99%
“…Este péptido fue descubierto primero en la soya y posteriormente en la cebada, trigo y recientemente en el centeno coreano (Jeong et al, 2009). La lunasina es quimiopreventiva y se indica que tiene efectos en la reducción del co lesterol (Gálvez, 2008).…”
Section: Aminoácidos Y Péptidosunclassified